Investigation of the scavenging process in two-stroke uniflow scavenging marine engines by a real-time multi-stage model - Liu, Dai; Han, Xiao; Liu, Long; Ma, Xiuzhen (Frontiers in Energy Research, 2022)
The increasing demand of digital twin marine engine requires real-time physical models for prediction. In two-stroke uniflow scavenging marine engines, a real-time physical model for scavenging process is rarely found since it is difficult to describe the complex in-cylinder air motion. Without accurate prediction of the fresh air loss and residual burned gas in the cylinder, the precision of combustion and emission simulation couldn’t be guaranteed as well. In marine engine digital twin system, scavenging ratio and fresh air skip are the vital results for further simulation of combustion and emission. To predict them in real-time, a novel zero-dimensional (0D) multi-stage scavenging model is proposed in this paper. In the cylinder zone, the complex gas motion is ideally divided to four stages: exhaust gas blowdown, perfect displacement, displacement-mixing and perfect mixing. The duration of each stage is determined by the engine design and control parameters. Then the thermodynamics conditions at each stage are simulated to obtain the mass of residual burned gas, fresh air inlet and outlet. The results of 0D model agree well with the results of CFD simulation, which indicates the potential for two-stroke marine engine digital twin system. It could also be applied in control-oriental engine model or engine diagnostic in the future.